Merçi de m'aider ex1) a)(+4)+(+2)= b)(-3)+(-12)= c)(-6)+(+2)= d)(+7)+(-12)= e)(+9,2)+2,5= f)(-0,4)+(-1,6)= ex2) A=(-3)+(+5)+(-14)+(-7)= B=(+12)+(+8)+(-13)+(-9)= C=(-14)+(-7)+(+2)+(-5)+(+7)= je remerçie ceux qui pourrons m'aider












































1

Réponses

2014-09-06T20:26:04+02:00
Bonsoir

ex1)

a) (+4)+(+2) = +4 + 2 = + 6
b) (-3)+(-12) = -3 -12 = -15
c) (-6)+(+2) = -6 + 2 = -4
d) (+7)+(-12) = +7 -12 = -5
e) (+9,2)+2,5 = +9,2 +2,5 = 11,7  
f) (-0,4)+(-1,6)= -0,4 - 1,6 = -2

ex2)

A= (-3)+(+5)+(-14)+(-7) = -3 + 5 -14 - 7 = -19  
B= (+12)+(+8)+(-13)+(-9) = +12 + 8 - 13 - 9 = -2
C= (-14)+(-7)+(+2)+(-5)+(+7) = -14 - 7 + 2 - 5 + 7 = -17